Association between Gestational Weight Gain Adequacy and Adverse Maternal and Neonatal Outcomes - Chen, Han-Yang; Chauhan, Suneet P. (American Journal of Perinatology, 2019)
Objectives To estimate the prevalence of gestational weight gain (GWG) adequacy according to the 2009 guidelines, and to examine the association between GWG adequacy and the adverse outcomes, stratified by prepregnancy body mass index (BMI).Study Design A retrospective cohort study, using the 2011 to 2013 U.S. linked birth/infant death datasets, restricted to nonanomalous singleton live births at 37 to 41 weeks. The adverse outcomes included composite maternal morbidity (CMM), composite neonatal morbidity (CNM), and neonatal and infant mortalities. We used multivariable Poisson's regression models with robust error variance to examine the association between GWG adequacy and adverse outcomes.Results Of 8,656,791 singleton live births, 20, 32, and 48% had inadequate, adequate, and excessive GWG, respectively. After multivariable regression adjustment, compared with adequate GWG, excessive GWG had 1.10 (1.08–1.13) and 1.12 (1.10–1.14) times higher risk of CMM and CNM, respectively; similar findings were observed in BMI subgroups. Compared with adequate GWG, inadequate GWG had 1.14 (1.03–1.26) and 1.12 (1.07–1.18) times higher risk of neonatal and infant mortalities, respectively. Similar results were noted among women with normal weight.Conclusion Excessive GWG was associated with an increased risk of CMM and CNM, while inadequate GWG was associated with a higher risk of neonatal and infant mortalities.
Keywords: body mass index; gestational weight gain; morbidity; mortality